Dynamics of the Hellenic Subduction Arc and Seismotectonic Stability of Eastern Libya: Stress Transmission and Seismic and Tsunami Hazards on the Cyrenaica Margin (Al-Farooq Journal of Sciences, 2026)
This study examines the seismotectonic stability of eastern Libya in light of the dynamics of the Hellenic subduction arc, one of the most active and complex subduction systems in the eastern Mediterranean. It is based on the hypothesis that the Cyrenaican margin and the northeastern coast of Libya, despite their distance from the direct subduction zone, do not constitute a geodynamically isolated margin. Rather, they lie within a zone of indirect influence related to Africa–Eurasia convergence, the subduction of the African slab, slab rollback, and the redistribution of tectonic stresses across the Mediterranean Ridge.The study adopts an integrated geodynamic–seismotectonic approach based on the analysis of slab geometry, the structural characteristics of the Hellenic subduction arc, and the southwestward motion of the Aegean block as indicated by geodetic measurements. It also examines the historical record of major seismic and tsunami events, as well as recent instrumentally recorded seismicity in the eastern Mediterranean. In addition, the study draws on Slab2 models, active fault databases, international earthquake catalogues, seismic hazard maps, and bathymetric data to interpret the relationship between regional tectonic structure and the seismotectonic sensitivity of the Cyrenaican margin.The findings indicate that the Hellenic subduction arc is not merely a distant seismic source relative to Libya, but rather a regional geodynamic system capable of indirectly influencing the seismotectonic stability of eastern Libya through the transfer and reorganization of stresses across the eastern Mediterranean. The study also shows that variations in slab geometry, slab rollback mechanisms, and the motion of the Aegean block generate a complex stress regime involving compression, extension, and strike-slip deformation. This regime is reflected in the patterns of seismic activity observed south of Crete, in the Aegean Sea, the Ionian Sea, and the Rhodes–Kos sector.The study further suggests that the geological structure of Cyrenaica, including inherited faults, carbonate formations, an elevated plateau, and a continental shelf connected to the Mediterranean basin, makes the region variably sensitive to changes in the regional stress field. These observations support an interpretive hypothesis that some aspects of fault reactivation and differential uplift along the Cyrenaican margin may be indirectly and testably related to the dynamics of Hellenic subduction and slab rollback, particularly through their role in reorganizing regional stresses within the eastern Mediterranean. The study also emphasizes that potential hazards along the eastern Libyan coast are not limited to local seismicity, but also include exposure to major regional seismic–tsunami events, as illustrated by the AD 365 Crete earthquake and its associated tsunami, which affected the southern shores of the Mediterranean.The study concludes that eastern Libya should be understood as a low- to moderate-sensitivity seismotectonic margin within an active regional system, rather than as a fully stable zone. It recommends strengthening seismic and geophysical monitoring networks, developing a national database of faults and tectonic structures, preparing probabilistic models for seismic and tsunami hazards, and integrating seismotectonic considerations into coastal urban planning and risk management policies, particularly in sensitive coastal cities such as Derna, Susa, and Tobruk.
Keywords: Hellenic subduction arc; seismotectonic stability; eastern Libya; Cyrenaica; tectonic stress transfer; fault reactivation; differential uplift; earthquakes; tsunami; slab rollback; coastal hazards